PERSEPSI GURU MENGENAI PEMBELAJARAN BERDIFERENSIASI DI SD NEGERI GANDASARI II - Anggunnissa Zulfiany Fachrina; Diah Gusrayani; Dadan Djuanda (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Teachers’ view on learning can affect the learning process. Differentiated learning can used for implement learning. Differentiated learning is a way of learning by paying attention to students’ need by conducting assessments and implemented learning in accordance with the students. Implementation of differentiated learning are still new at school makes some teachers are still figure it out what is differentiated learning and how to implemented it at class. Based on that, the researcher wantsto give an overview of teacher perceptions of differentiated learning among elementary school teacher at Gandasari II elementary school. This research used a qualitative approach with a case study method to find out the overview of teachers’ perceptions in school. The intended participants in this research are teacher who had implemented differentiated learning, classes I, II, IV, and V at Gandasari II elementary school. Data were collected through interviews and observations. To analyze data researchersselected data, presented data, dan drew conclusions. Based on research data, teachers already had a positive perception of differentiated learning. It’s seen from the teacher’s perception that it already matches the concept of differentiated learning. However, in the application of differentiated learning there are several things that are not in line with the concept of differentiated learning. The obstacles experienced by teachers vary, which are found at the beginning, implementation, and end of learning.